Narratives of Radicalism in Madurese Society Examined Through Symbolic Interactionism - Moch Tohet; Muhammad Zainuddin Sunarto (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study aims to analyze how the narrative of radicalism develops and influences social harmony among the Madurese ethnic community in Probolinggo Regency, using a symbolic interactionism perspective. The research is based on the assumption that a society with a majority Madurese ethnic population has strong social and cultural ties, but also faces the potential for radicalization due to economic injustice and the influence of conservative ideology. This study uses a qualitative approach with a phenomenological method, involving in-depth interviews, direct observation, and document analysis as data collection techniques. The findings show that radicalism in Madurese society is mostly spread through social interactions within families and communities, with an important role for religious authority figures, such as kyai. This study contributes to a deeper understanding of the role of social interaction and symbols in shaping the narrative of radicalism, as well as providing insights for efforts to prevent radicalization by strengthening social harmony at the community level.